Autosomal Recessive Malignant Infantile Osteopetrosis Associated with a TCIRG1 Mutation: A Case Report of a Neonate Presenting with Hypocalcemia in South Korea - Yun Kyo Oh; Koung Eun Choi; Youn-Jeong Shin; Eun Ryoung Kim; Ji Yeon Kim; Min Sun Kim; Sung Yoon Cho; Dong Kyu Jin (Korean Society of Neonatology, 2021)
Osteopetrosis refers to a group of genetic skeletal disorders characterized by osteosclerosis and fragile bones. Osteopetrosis can be classified into autosomal dominant, autosomal recessive, or X-linked forms, which might differ in clinical characteristics and disease severity. Autosomal recessive osteopetrosis, also known as malignant osteopetrosis, has an earlier onset, more serious clinical symptoms, and is usually fatal. We encountered a 1-day-old girl who was born full-term via vaginal delivery, which was complicated by meconium-stained amniotic fluid, cephalo-pelvic disproportion, and nuchal cord. Routine neonatal care was provided, in addition to blood tests and chest radiography to screen for sepsis, as well as skull radiography to rule out head injuries. Initial blood tests revealed hypocalcemia, which persisted on follow-up tests the next day. Radiographic examinations revealed diffusely increased bone density and a "space alien" appearance of the skull. Based on radiographic and laboratory findings, the infantile form of osteopetrosis was suspected and genetic testing for identification of the responsible gene. Eventually, a heterozygous mutation of the T cell immune regulator 1, ATPase H+ transporting V0 subunit a3 (TCIRG1) gene (c.292C>T) was identified, making this the first reported case of neonatal-onset malignant osteopetrosis with TCIRG1 mutation in South Korea. Early-onset hypocalcemia is common and usually results from prematurity, fetal growth restriction, maternal diabetes, perinatal asphyxia, and physiologic hypoparathyroidism. However, if hypocalcemia persists, we recommend considering 'infantile of osteopetrosis' as a rare cause of neonatal hypocalcemia and performing radiographic examinations to establish the diagnosis.